Salivary Oxytocin Concentrations in Seven Boys with Autism Spectrum Disorder Received Massage from Their Mothers: A Pilot Study - Tsuji, Shuji; Yuhi, Teruko; Furuhara, Kazumi; Ohta, Shogo; Shimizu, Yuto; Higashida, Haruhiro (Frontiers in Psychiatry, 2015)
Seven male children with autism spectrum disorder (ASD), aged 8 – 12 years, attending special education classrooms for ASD and disabled children, were assigned to receive touch therapy. Their mothers were instructed to provide gentle touch in the massage style of the International Liddle Kidz Association. The mothers gave massages to their child for 20 minutes every day over a period of 3 months followed by no massage for 4 months. To assess the biological effects of such touch therapy, saliva was collected before and 20 minutes after a single session of massage for 20 minutes from the children and mothers every 3 weeks during the massage period and every 4 weeks during the non-massage period, when they visited a community meeting room. Salivary oxytocin levels were measured using an enzyme immunoassay kit. During the period of massage therapy, the children and mothers exhibited higher oxytocin concentrations compared those during the non-massage period. The changes in oxytocin levels before and after a single massage session were not significantly changed in children and mothers. The results suggested that the ASD children (massage receivers) and their mothers (massage givers) show touch therapy-dependent changes in salivary oxytocin concentrations.